Se transporter dans l’autre" : une théorie weilienne de l’empathie ? - Delanoy, Blandine (Labyrinth, 2024)
Defined as the ability to understand and share others' feelings and suffering, empathy seems to come naturally to mind when we consider Simone Weil's life and works. If this concept doesn't explicitly appear in her writings, "pity", "sympathy" and "compassion" are pervasive: the purpose of this paper is to demonstrate how these notions converge on the contemporary understanding of "empathy". Since the turn of the century, this concept has known such a development that it has become difficult to clearly identify its object, and to appreciate its ethical value. To study Simone Weil's works from the angle of empathy offers both a new approach of the concept, and a very relevant point of view to put in light the great continuity between all the fields of the philosopher's thought. Our main hypothesis is that the weilian theory of empathy is based on the idea of "transposition", a process that allows someone to transport himself into another person, and from the natural to the supernatural dimension. It is in this last dimension that Simone Weil can found intersubjectivity, and solve the ethical problem of empathy: the right distance between the Self and the Other.